Carlos Riobó. Caught between the Lines: Captives, Frontiers, and National Identity in Argentine Literature and Art. U of Nebraska P, 2019. - Manuela Borzone (Studies in 20th & 21st Century Literature, 2021)
Review of Carlos Riobó. Caught between the Lines: Captives, Frontiers, and National Identity in Argentine Literature and Art. U of Nebraska P, 2019. xii +180 pp.
Keywords: Southern Cone; Argentina; frontier; captives